Impact of granules from crushed expanded polystyrene package on properties of thermo-insulating plaster - Šeputytė-Jucikė, Jurga; Sezeman, Georgij Arsenij; Sinica, Marijonas; Kligys, Modestas; Vaitkus, Saulius (Journal of Civil Engineering and Management, 2014)
The paper deals with the use of lightweight porous aggregate, i.e. crushed expanded polystyrene package crumbs (EPSC) in the composition of thermo-insulating plaster. Its effectiveness is compared to that of spherical granules of expanded polystyrene – white coloured (EPS) and grey coloured (NEOPOR). The content of lightweight aggregate changed from 1.25 to 1.75 l/kg of dry mix. The investigation focused on properties of modified plaster, such as density, compressive strength, thermal conductivity and water vapour permeability. It was established that EPSC reduce density of plaster from 1350 to 530 kg/m3, improving such properties as thermal conductivity and water vapour permeability but decreasing compressive strength. In addition, the paper established the adhesion force of plaster (content of lightweight aggregate was 1.25 l/kg of dry mix) to ceramics, silicate and autoclaved aerated concrete masonry elements. The character of macrostructure of plaster was considered, as well as bonding with a coat of decorative paint. It was found that plaster with EPSC has similar properties to plasters with EPS and NEOPOR aggregates; however, in case of EPSC, the relative vapour resistance is better. The provided regression equations can be used for prediction of differently modified plasters.